The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1042/bst20190675
|View full text |Cite
|
Sign up to set email alerts
|

Membrane-anchored serine proteases as regulators of epithelial function

Abstract: Cleavage of proteins in the extracellular milieu, including hormones, growth factors and their receptors, ion channels, and various cell adhesion and extracellular matrix molecules, plays a key role in the regulation of cell behavior. Among more than 500 proteolytic enzymes encoded by mammalian genomes, membrane-anchored serine proteases (MASPs), which are expressed on the surface of epithelial cells of all major organs, are excellently suited to mediate signal transduction across the epithelia and are increas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
18
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 103 publications
0
18
0
Order By: Relevance
“…As part of this family, there is a subgroup composed of membrane-anchored serine proteases, which is divided into (i) GPI-serine proteases that are anchored in the plasma membrane by a glycosylphosphatidylinositol anchor, (ii) Type I-serine proteases that have a single pass domain in the plasma membrane located close to the C-terminus end, and (iii) Type II-serine proteases that are anchored in the plasma membrane and have an anchor sign located close to the N-terminus end [77,82].…”
Section: Proteases and Hpv Carcinogenesismentioning
confidence: 99%
See 1 more Smart Citation
“…As part of this family, there is a subgroup composed of membrane-anchored serine proteases, which is divided into (i) GPI-serine proteases that are anchored in the plasma membrane by a glycosylphosphatidylinositol anchor, (ii) Type I-serine proteases that have a single pass domain in the plasma membrane located close to the C-terminus end, and (iii) Type II-serine proteases that are anchored in the plasma membrane and have an anchor sign located close to the N-terminus end [77,82].…”
Section: Proteases and Hpv Carcinogenesismentioning
confidence: 99%
“…Different studies have shown that when matriptase is less expressed, there is also less activation of uPA in the cells of ovary and prostate cancer [87,88]. Matriptase is also responsible for activating the PI3K-Akt-mTOR pathway after the proteolytic activation of the hepatocyte growth factor precursor (pro-HGF), which can promote cell proliferation and decrease apoptosis [82]. PAR-2 (protease-activated receptor 2), a receptor expressed in different cell types, is related to cell adhesion, the maintenance of the skin barrier, and inflammatory responses [89,90].…”
Section: Proteases and Hpv Carcinogenesismentioning
confidence: 99%
“…Importantly, in expression systems ENaC can be fully activated by coexpressing membraneanchored serine proteases (43)(44)(45)(46). The family of membrane-anchored serine proteases consists of 20 members identified in human to date (47)(48)(49). They share a conserved extracellular catalytic domain and J o u r n a l P r e -p r o o f 4 are anchored directly to the plasma membrane via a GPI-anchor or a transmembrane domain.…”
Section: Introductionmentioning
confidence: 99%
“…Depending on the similarity in modular arrangements in the stem region, TTSPs can be divided into four subgroups, that is, hepsin (also known as TMPRSS1), matriptase, HAT, and corin subgroups [12,13]. Members of the TTSP family are expressed in many tissues, where they participate in diverse processes, including food digestion [14], epithelial differentiation [15,16], intestinal barrier function [17][18][19], skin permeability [20][21][22], sodium homeostasis [23,24], iron metabolism [25], and vascular remodeling [26,27]. TTSP deficiencies or overexpression has been reported in patients with malnutrition [14], skin defects [28,29], intestinal disease [30], iron deficiency anemia [25], hypertension [31,32], kidney disease [33], and cancer [34].…”
Section: Introductionmentioning
confidence: 99%